2021
DOI: 10.48550/arxiv.2106.10224
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A new approach to proper orthogonal decomposition with difference quotients

Abstract: In a recent work [B. Koc et al., arXiv:2010.03750, SIAM J. Numer. Anal., to appear], the authors showed that including difference quotients (DQs) is necessary in order to prove optimal pointwise in time error bounds for proper orthogonal decomposition (POD) reduced order models of the heat equation. In this work, we introduce a new approach to including DQs in the POD procedure. Instead of computing the POD modes using all of the snapshot data and DQs, we only use the first snapshot along with all of the DQs a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
5
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(6 citation statements)
references
References 40 publications
(72 reference statements)
1
5
0
Order By: Relevance
“…These temporal derivatives can be easily computed using the righthand side of the mixed finite element Galerkin equation. In the present paper we follow an idea presented in the recent paper [22] in which it is shown that there is no need to include in the set of snapshots other than one approximation to the velocity at a fixed time, instead of the full set u h (t j ) M j=0 as it is usually done in the literature. The numerical analysis in [22] is carried out for the heat equation and with difference quotients, (u h (t j ) − u h (t j−1 )/(t j − t j−1 ) , approaching the time derivative.…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…These temporal derivatives can be easily computed using the righthand side of the mixed finite element Galerkin equation. In the present paper we follow an idea presented in the recent paper [22] in which it is shown that there is no need to include in the set of snapshots other than one approximation to the velocity at a fixed time, instead of the full set u h (t j ) M j=0 as it is usually done in the literature. The numerical analysis in [22] is carried out for the heat equation and with difference quotients, (u h (t j ) − u h (t j−1 )/(t j − t j−1 ) , approaching the time derivative.…”
Section: Introductionmentioning
confidence: 99%
“…In the present paper we follow an idea presented in the recent paper [22] in which it is shown that there is no need to include in the set of snapshots other than one approximation to the velocity at a fixed time, instead of the full set u h (t j ) M j=0 as it is usually done in the literature. The numerical analysis in [22] is carried out for the heat equation and with difference quotients, (u h (t j ) − u h (t j−1 )/(t j − t j−1 ) , approaching the time derivative. In the present paper we consider instead the Galerkin time derivatives although the analysis for the difference quotients case is essentially the same (or even simpler).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations